Anti-inflammatory and analgesic effects of trachyspermum ammi seed extract and Its GC-MS analysis - Aslam, Adeel; Nokhala, Ahmed; Peerzada, Sohaib; Ahmed, Shoaib; Khan, Tanveer; Siddiqui, Mohammad Jamshed Ahmad (Medknow, 2020)
Introduction: Since ancient times Trachyspermum ammi was utilized for its anti-inflammatory and analgesic effects in traditional medicine system. Objectives: Present study aimed to evaluate the anti-inflammatory and analgesic effect and characterization of chemical composition seed extract of T. ammi through GC-MS. Material and Methods: Seed extracts were prepared through soxhlet extraction using n-hexane, chloroform and methanol as solvents. Gas chromatography-mass spectroscopy (GCMS) analysis was performed by derivatized sample of T. ammi extract. Acute toxicity test performed at dose of 400mg/kg, 800mg/kg, 1600mg/kg and 3200mg/kg. Two different strengths (minimum therapeutic dose 500mg/ kg and maximum therapeutic dose1000mg/kg) were given to Wistar rats to measure anti-inflammatory and analgesic activity. Results: Results from analgesic and antiinflammatory activity demonstrate that in both activities standard drug (tramadol) have more analgesic (percentage of analgesia 26.08%) and regarding anti-inflammatory effect diclofenac sodium (percentage of inhibition of paw edema 29.68%) more effective as compared to test drug. When efficacy of all extracts compared with each other n-hexane extract showed more percentage of inhibition (percentage analgesia 20.69% and percentage inhibition of paw edema 22.21%) at maximum effective dose 1000mg/kg. In order to find out significance difference among groups ANOVA test was used at 95% significant level. A number of different bioactive compounds were identified through GC-MS analysis. Conclusion: Results showed that T. ammi seed extracts have anti-inflammatory and analgesic activity potentiating in neurotransmission of GABA and repression of receptor of glutamate along with suppression of nitric oxide (NO) pathway. Phenolic compounds present in seeds may responsible for anti-inflammatory activity.